Control System Strategy Of The Saponification Process Between Ethyl Acetate And Sodium Hydroxide - M. Djaeni; Suherman Suherman; K. Jalasanti; R. R. Mukti (Reaktor, 2001)
The research looks into the performance of Proportional (P), Proportional Integral (PI), and Proportional Integral Derivative (PID) controller to maintain soap concentration. To facilitate the study, the mathematical model of saponification process is derived using information cited from literature. Then the model is validated using experimental data. Based on model, the control system using Proportional (P), Proportional Integral (PI) and Proportional Integral Derivative (PID) are designed. In this case, the constant of each controller is tuned using Ziegler Nichols method. The result showed that the PID controller with Integral Square Error (ISE) of 5,77936 E-08 isthe strongest for disturbance rejection among the others. The performance of PID controlleris also good for set point tracking with ISE of 1.28227 E-05.Key words : control, mathematical model, simulation, saponification